Task-based essay writing material: Integrating global Englishes into English language teaching - Anggara Jatu Kusumawati; Dwi Yulianto Nugroho (Universitas Ahmad Dahlan, 2026)
This study explores how essay writing material integrating task-based approach and Global Englishes (GE) in English Language Teaching (ELT). Native-speaker norms and prescriptive standards are often emphasized in traditional writing pedagogy especially in higher education contexts, neglecting learners’ multilingual repertoires and the role of English as a global lingua franca. Due to this gap, Task-Based Language Teaching (TBLT) framework was used to design materials to scaffold academic writing skills and to justify students’ multilingual repertoires. Employing a qualitative case study, this study shows how TBLT and diverse English varieties can be integrated into essay writing tasks using data from needs analysis, classroom observations, and student feedback. This study involved our lecturers and fifty-three undergraduate students in an essay writing course, who share similar backgrounds and regularly use multiple languages. The findings show that (1) students participated more actively in writing tasks, (2) they demonstrated greater critical awareness of multilingual English use in their reflections and essays, and (3) they expressed increased confidence in using their own linguistic resources. The module also addresses the limitations of monolingual writing conventions in the Indonesian higher education context. Overall, the study shows that TBLT is an effective approach for integrating GE into writing classrooms. Aligning academic pedagogy with the sociolinguistic diversities of GE was the implication for material developers, teachers, and institutions.